The Role of Teachers in Shaping Students' Attitudes of Responsibility in Pancasila and Civics Education Learning at SMP Negeri 12 Malang - Stefania Lele Gesi; Yulius Rustan Effendi; Romadhon Romadhon (CV Projurnal Mitra Publikasi, 2025)
The role of teachers in shaping learners‘ attitudes of responsibility in learning Pancasila and Civics Education, can gain a deeper understanding of effective ways to instil these important values, which in turn can have a positive impact on the development of learners’ character and the overall quality of education. In addition, this research can reveal the challenges faced by teachers in shaping learners' attitudes of responsibility and the opportunities that exist to overcome them. The researcher used a descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation studies. The research findings show that the role of teachers in shaping the attitude of responsibility through various approaches, including a personal approach, providing direct education, involving students in learning, and organising group work and PPK activities in the morning. The challenges faced include the character of students who are difficult to guide and the lack of support from families. The solution to overcome the inhibiting factors is that teachers take a personal approach, Civics teachers coordinate and cooperate with homeroom teachers and counseling teachers, Civics teachers also make visits to students‘ homes to talk directly with students’ parents to discuss problems and find the right solution.